Growth, volatility and political instability: non-linear time-series evidence for Argentina, 1896 - 2000 - Nauro F. Campos; Menelaos G. Karanasos (Institute for the Study of Labor (IZA), 2007)
What is the relationship between economic growth and its volatility? Does political instability affect growth directly or indirectly, through volatility? This paper tries to answer such questions using a power-ARCH framework with annual time series data for Argentina from 1896 to 2000. We show that while assassinations and strikes (what we call informal political instability) have a direct negative effect on economic growth, formal political instability (constitutional and legislative changes) has an indirect (through volatility) negative impact. We also find preliminary support for the idea that while the effects of formal instability are stronger in the long-run, those of informal instability are stronger in the short-run.
Keywords: 320; Economic growth; volatility; political instability; power-ARCH; Wirtschaftswachstum; Volatilität; Politische Stabilität; Schätzung; Argentinien